Contando (Buenos Aires : Sigmar, 2009)
Fotos de verduras, juguetes, y otros objetos introducen el concepto de contar.
Photographs of fruits, toys, and other objects introduce the concept of counting.
Translation of: My first look at-- counting.
Text in Spanish.
Keywords: Counting -- Juvenile literature; Contar (Enumerar) -- Literatura juvenil